A hybrid sub-lineage of Listeria monocytogenes comprising hypervirulent isolates - Yuelan Yin (Nature Portfolio, 2019)
Listeria monocytogenes isolates are highly heterogeneous and exhibit different levels of virulence. Here, the authors identify hypervirulent isolates that represent a hybrid sub-lineage of the major lineage II harbouring virulence factors from Listeria ivanovii and wall teichoic acids found in major lineage I.